Temporal evolution of human mercury exposure in the Amazon: A scientometric approach - Serra , Clarisse Vasconcellos; Figueiredo, Wllyane da Silva; Bernardi , José Vicente Elias (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
Due to the current global attention to mercury exposure and toxicity, as well as its various consequences on ecosystems and human health, new scientometric tools help to better understand the issues involved. In this literature research, studies of the risk of human exposure to mercury in populations of the Brazilian Amazon biome in the last three decades were contemplated using scientometric techniques, bibliographic docking, authors, citations, and keywords. The analyses of the period from 1991 to 2019 enabled the selection of 130 articles. There was the identification of the main research institutions, classification and interrelations of the main thematic axes of the studies in the Amazon biome and most cited authors. The most referenced articles on this theme and the main bioindicators were ordered. The results show that most of the studies were carried out along rivers and with riverside populations. In the sample universe, there is a predominance of localities on the Tapajós and Madeira Rivers. Most researchers work only with internal partnerships, without interaction with other scientific groups. The hair matrix is the main bioindicator of Hg exposure used by the authors. For future perspective, this paper has the potential to represent a general temporal understanding of human exposure to mercury in the Amazon and its main bioindicators.